Quality of life and associated factors in non-institutionalized elderly: a cross-section study (Research, Society and Development, 2021)
The aim this study was to analyze the quality of life (QoL) and its the association with sociodemographic and oral health data in non-institutionalized elderly individuals. This is a cross-sectional study with a sample of 225 elderly individuals aged 60 years or older from a city in Southern Brazil. For data collection, we used the quality of life scale (WHOQOL-OLD), the Geriatric Oral Health Assessment Index (GOHAI), as well as questions about sociodemographic and oral health conditions. QoL presented a mean of 62.73. Sociodemographic variables were tested in a linear regression model, and those that remained associated in the final adjusted model were: age (β = -0.25; 95% confidence interval, CI: -0.40; -0.14), daily independence (β = -0.32; 95% CI: -7.71; -3.57), and participation in social activities (β = -0.12; 95% CI: -4.31; -0.21). The elderly individuals’ oral characteristics were compared, and the following remained associated in the adjusted model: time of last visit to the dentist (β = -0.34; 95% CI: -9.50; -4.65) and oral self-perception (β = 0.30; 95% CI: 0.53; 1.18).The findings of this study showed that, being older, being dependent in life and non-participating in social activities, as well as no visiting the dentist last year were predictors of a worst QoL for the elderly, however, good self-perception of oral health was a predictor of better QoL.